SEXUAL DISHARMONY COUPLES IN WHICH THE WOMAN IS ILL SCHIZOTYPAL DISORDER - Животовська, Л.В.; Сонник, А.Є. (World of Medicine and Biology, 2015)
The problem of psychosomatic relations in any pathology is one of the most actual problems of medicine because of medical observation and influence aimed, on the one hand - on the human body, and on the other to its socio-psychological sphere - identity. Sexual disharmony spouses may occur not only because of the existing pathology, but also through the exclusion of a particular level of their interaction. The aim of the study was to investigate the sexual health of couples where the family has a place of sexual disharmony and the woman suffers schizotypal disorder, as well as to clarify the role of endogenous process in women in disharmony development. Under our observation were 27 couples with sexual disharmony, in which the woman is ill schizotypal disorder diagnostic criteria ICD-10 (F21). Conducted a comprehensive examination, including clinical-anamnestic and special sexological research using a systematic structural analysis of sexual health. Duration of sexual maladjustment 27 couples were 3-9 years and had a direct relation between the duration of illness. Women’s studies showed that their average age was 39±7,6 years, duration of disease was within 15±5,3 years. 10 (37,1%) of women with a clinical picture was characterized by neurosis-like symptoms, which prevailed mental exhaustion, overvalued attitude towards their health. Sexual status was noted disharmony of sexual life, decreased interest in sex partner in 4 (14,8%) of cases there was a decrease in sensitivity in the genital area. The clinical picture 9 (33,3%) surveyed in the first plan were psychopathology symptoms in the form of vagrancy, prone to emotional outbursts, lack of adaptation to the environment. Sexually noted a variety of disorders: Hyper - or hyposexuality, disinhibition of sexual desire and the retardation psychosexual development, sexual fantasy and abstract imagination. In all cases, patients reported that they do not receive pleasure from sexual activity. The clinical picture in 8 (29,6%) surveyed dominated hypochondriac symptoms with the belief that in some severe disease, which relied on numerous, severe, painful, unpleasant sensations in the whole body. In the sexual status of these patients had a change interpersonal relationships, fears of sexual relations with preserved libido, fear of Contracting a sexually transmitted disease, decreased interest in sex partner. We conducted a systematic structural analysis of sexual health has allowed to identify the status of components and sexual disharmony in married pairs and set its severity in women and men. 11 (40,8%) couples exclusion arose through sexual dysfunction due to traumatic experiences in women who suffer schizotypal disorder. In this case the cause of sexual maladjustment was pivotal defeat the psychic component of the biological component of sexual health. In 7 (25,9%) of couples sexual dysfunction was noted through lack of awareness of one or both in matters of mental health, sexual life. Dominant in its origin was the defeat of the social component in the form of information and evaluation component, due to the low level of knowledge of the spouses in matters of mental health, sexual life, misconceptions about normal and pathological physiological fluctuations in sexual function and/or incorrect assessment of the spouses of their sexual manifestations. Sexual maladjustment 9 (33,3%) of couples was caused by a low level of socio-psychological adaptation. The main reason in this case was pivotal defeat of the psychological component of sexual harmony in the presence of one of the spouses character traits that are not perceived by another person. Thus, schizotypal disorder causes of sexual disorders in women and provokes the development of marital disharmony, which is based on a complex multifactorial etiopathogenesis, which includes biological, psychological and socio-psychological phenomena. The combination of unfavorable personality traits of the couple can be disharmonious factor in the relationship and/or deepen the development of sexual maladjustment. The obtained data can be taken into account when carrying out complex treatment and rehabilitation and psycho events this contingent of patients.